Peningkatan Kompetensi Creative, Communication, Colaboration Dan Critical Thinking (4C) Generasi Milenial - Putri Ayu Permata Devi; Titis Sri Wulan; Reni; Mochamad Rizki Sampoerno (CV. Multi Kreasi Media, 2023)
The Millennial Generation, born between the 1980s and early 2000s, plays an essential role in today’s workplace and society. They grew up in the era of information technology and are connected globally. Therefore, they have great potential to make creative contributions, collaborate and think critically. This community service aims to improve the primary skills of the millennial generation, especially creativity, communication, collaboration and critical thinking. These skills need to be improved so that the millennial generation can play a more effective role in facing the challenges of the contemporary world. The service modality used is by holding seminars and training for class XII of SMA Negeri 1 Anyer, Banten. Case studies are conducted to explore examples of best practices that can be implemented to improve these skills. The results of this activity show that training is crucial to improving the skills of the millennial generation. Apart from that, the application of digital technology and project-based learning can also help develop Millennial generation’s creativity, communication, collaboration and critical thinking abilities. This activity makes an essential contribution to understanding how to improve the skills of the millennial generation so that it will positively impact the development of these crucial skills. The millennial generation can be a more effective driver of change to overcome various challenges in the era of globalization and continuous technological development.